High-thermal-conductivity PI / ceramic composite insulation packaging sheet and preparation method thereof
A modified PI/ceramic composite insulation layer addresses the need for high thermal conductivity and insulation by uniformly dispersing ceramic particles in a polyimide matrix, ensuring stability and thermal efficiency in electronic applications.
Patent Information
- Application Number
- CN202510593285.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-09
- Publication Date
- 2025-07-15
AI Technical Summary
In the prior art, composite materials such as diamond/copper, SiC/Al cannot effectively dissipate heat in applications requiring insulation or dielectric properties due to the existence of metal substrates, resulting in thermal management materials being unable to meet the dual needs of thermal conductivity and insulation in high-performance and high-integration electronic components.
Modified polyimide solution and modified ceramic particles are mixed in a specific proportion, and a high-thermal conductivity PI/ceramic composite insulated packaging sheet is prepared by high-temperature curing. During the modification process, hydroxymethylacrylamide is introduced to form C-O-C bonds and hydrogen bonds with the hydroxyl groups on the ceramic surface to promote the dispersion of ceramic particles and form a chemical covalent bond network to improve heat conduction efficiency.
The prepared packaging sheet has high thermal conductivity, stability and good insulation properties, can remain stable at high temperatures, and is not prone to thermal deformation, and is suitable for thermal management of high-power electronic components.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic packaging, and particularly to a high thermal conductivity PI / ceramic composite insulating packaging sheet and a preparation method thereof. Background Art
[0002] In recent years, electronic components have been developing towards high performance and high integration. Along with this, the heating power of electronic components has been continuously increasing, and various microelectronic technology application fields have further requirements and dependencies on thermal management materials.
[0003] In the prior art, composite materials such as diamond / copper and SiC / Al, as a new generation of thermal management materials, have high thermal conductivity and appropriate thermal expansion coefficients. However, due to the presence of a metal matrix, they cannot be used in application scenarios that require specific insulation or dielectric properties. For example, in addition to electrical insulation, an integrated circuit substrate also requires a material with high thermal conductivity to dissipate heat in a timely manner to meet the requirements of high power. Therefore, there is an urgent need to develop a composite packaging material that combines high thermal conductivity and insulation performance. Summary of the Invention
[0004] The purpose of the present invention is to provide a high thermal conductivity PI / ceramic composite insulating packaging sheet and a preparation method thereof to solve the problems existing in the prior art.
[0005] To solve the above technical problems, the present invention provides the following technical solution: A high thermal conductivity PI / ceramic composite insulating packaging sheet, which is obtained by high-temperature curing after mixing a modified polyimide solution and modified ceramic particles in a mass ratio of 9 - 13:1; The modified polyimide solution is obtained by mixing a dianhydride monomer and a diamine monomer in a molar ratio of 1:1, and 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester with a total molar amount of 5% - 10%, and then adding a catalyst for catalysis; The modified ceramic particles are obtained by adding hydroxymethylacrylamide to a ceramic suspension, followed by filtration, washing, and drying.
[0006] Further, the catalyst includes acetic anhydride and pyridine.
[0007] Further, the ceramic particles include alumina ceramic particles, aluminum nitride ceramic particles, or silicon carbide ceramic particles.
[0008] Further, the ceramic suspension is obtained by mixing ceramic particles and deionized water in a mass ratio of 1:10 - 15 and adding a dispersant accounting for 1% - 3% of the mass of the ceramic particles.
[0009] Further, the dispersant is sodium polyacrylate, sodium hexametaphosphate, or polyvinylpyrrolidone.
[0010] Further, a preparation method of a high thermal conductivity PI / ceramic composite insulation encapsulation sheet includes the following preparation steps: (1) Mix the dianhydride monomer and the diamine monomer in a molar ratio of 1:1, then add 60%-70% of the organic solvent based on the total mass fraction, and mix and stir at 20°C - 30°C for 30 - 60 minutes with the rotation speed controlled at 300 - 500 r / min; slowly raise the temperature to 50 - 60°C and react for 2 - 3 hours to carry out the amidation reaction, and add 30%-50% of the acid-binding agent based on the molar amount of the dianhydride monomer to neutralize the acid generated by the reaction; then add 5%-10% of 2-methyl-2-acryloyloxy-1,3-dihydroxypropane based on the total molar amount of the raw materials, raise the temperature to 80 - 90°C, and stir and react for 3 - 4 hours to obtain a polyamic acid prepolymer solution; then add a catalyst to the polyamic acid prepolymer solution and react at 80 - 100°C for 4 - 6 hours to obtain a modified polyimide solution; (2) Select ceramic particles with a particle size of 50 - 100 nm, add them to deionized water according to the mass ratio of 1:10 - 15 to that of deionized water, then add 1%-3% of the dispersant based on the mass of the ceramic particles, stir at a stirring speed of 800 - 1000 r / min for 20 - 40 minutes, and then ultrasonically treat at a power of 300 - 400 W for 40 - 60 minutes to obtain a ceramic suspension; add hydroxymethylacrylamide to the ceramic suspension, and the molar ratio of hydroxymethylacrylamide to the hydroxyl groups on the ceramic surface is 1 - 2.5:1, raise the temperature of the reaction system to 70 - 80°C, and react at a stirring speed of 500 - 600 r / min for 4 - 5 hours, then filter, wash, and dry to obtain modified ceramic particles; (3) Add the modified ceramic particles obtained in step (2) to the modified polyimide solution obtained in step (1) according to the mass ratio of 9 - 13:1 of the modified polyimide solution to the modified ceramic particles, stir at a stirring speed of 600 - 800 r / min for 20 - 40 minutes to obtain a dispersion solution; coat the dispersion solution on a stainless steel mold with the coating thickness controlled at 0.2 - 0.5 mm; then cure at high temperature to obtain an encapsulation sheet.
[0011] Further, in step (1), adding a catalyst to the polyamic acid prepolymer solution and reacting at 80 - 100°C for 4 - 6 hours to obtain a modified polyimide includes: adding acetic anhydride with 1.5 - 2 times the molar amount of carboxyl groups in the polyamic acid prepolymer and 0.5 - 1 times the molar amount of pyridine of the acetic anhydride as a catalyst to the polyamic acid prepolymer solution, and reacting at 80 - 100°C for 4 - 6 hours to obtain a modified polyimide.
[0012] Further, in the step (1), the preferred value of 2,3 - dihydroxypropyl 2 - methyl - 2 - acrylate in the total molar amount is 8%.
[0013] Further, in the step (2), the molar ratio of hydroxymethylacrylamide to the hydroxyl groups on the ceramic surface is preferably 2:1.
[0014] Further, in the step (3), the mass ratio of the modified polyimide solution to the modified ceramic is preferably 11:1.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: 2,3 - Dihydroxypropyl 2 - methyl - 2 - acrylate is added to the dianhydride monomer and diamine monomer to prepare a modified polyimide. The modified polyimide contains hydroxyl groups and carbon - carbon double bonds. The carbon - carbon double bonds participate in the cross - linking reaction during subsequent curing to form a chemical covalent bond network, so as to improve the mechanical properties and heat resistance of the polyimide matrix; the ceramic is pretreated to obtain a ceramic suspension, and then hydroxymethylacrylamide is added. The hydroxymethyl in hydroxymethylacrylamide condenses with the hydroxyl groups on the ceramic surface to form a C - O - C bond, and at the same time the amide group (-CONH2) is exposed on the surface to prepare a modified ceramic. The modified ceramic is added to the modified polyimide solution. The carbon chain structure and amide group of hydroxymethylacrylamide form a flexible protective layer on the ceramic surface, which can prevent the direct contact between ceramic particles through steric hindrance, so that the ceramic is uniformly dispersed in the polyimide solution; moreover, the amide group on the surface of the modified ceramic forms hydrogen bonds with the hydroxyl groups of the polyimide, further promoting the dispersion of ceramic particles, forming a dense interfacial layer through chemical bonding, reducing the interfacial thermal resistance and improving the heat conduction efficiency. The prepared encapsulation sheet has high thermal conductivity, remains stable at a relatively high temperature, is not prone to thermal deformation, and has strong stability. Specific embodiments
[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative work shall fall within the protection scope of the present invention.
[0017] In order to more clearly illustrate the method provided by the present invention, the following examples are used for detailed description: Example 1 (1) Mix pyromellitic dianhydride and p-phenylenediamine at a molar ratio of 1:1, then add 60% of the total mass fraction of N,N-dimethylformamide, and mix and stir at 25 °C for 40 minutes with the rotation speed controlled at 450 r / min; slowly raise the temperature to 60 °C and react for 3 hours to carry out an amidation reaction, and add 40% of triethylamine in terms of the molar amount of pyromellitic dianhydride to neutralize the acid generated by the reaction; then add 5% of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester in terms of the total molar amount of the raw materials, raise the temperature to 90 °C, and react at a stirring speed of 500 r / min for 4 hours to obtain a polyamic acid prepolymer solution; then add acetic anhydride with a molar amount twice that of the carboxyl groups in the polyamic acid prepolymer and 0.5 times the molar amount of acetic anhydride of pyridine to the polyamic acid prepolymer solution, and react at 80 °C for 6 hours to obtain a modified polyimide solution; (2) Select alumina ceramic particles with a particle size of 80 nm, add them to deionized water according to the mass ratio of 1:15 to that of deionized water, then add 1% of polyvinylpyrrolidone based on the mass of the alumina ceramic particles, stir at a stirring speed of 1000 r / min for 40 minutes, and then perform ultrasonic treatment at a power of 400 W for 60 minutes to obtain an alumina ceramic suspension; add hydroxymethylacrylamide to the alumina ceramic suspension, and the molar ratio of hydroxymethylacrylamide to the surface hydroxyl groups of the alumina ceramic is 1:1, raise the temperature of the reaction system to 80 °C, react at a stirring speed of 500 r / min for 5 hours, then carry out vacuum filtration under a vacuum degree of -0.06 MPa, and then wash with deionized water 3 - 5 times to remove impurities, and then dry at 60 °C for 8 hours to obtain modified alumina ceramic particles; (3) Add the modified alumina ceramic particles obtained in step (2) to the modified polyimide solution obtained in step (1) at a mass ratio of the modified polyimide solution to the modified alumina ceramic particles of 9:1, and stir at a stirring speed of 800 r / min for 40 minutes to obtain a dispersion solution; coat the dispersion solution on a stainless steel mold, and control the coating thickness at 0.5 mm; then cure at 200 °C for 4 hours to obtain a packaging sheet.
[0018] Example 2 (1) Mix pyromellitic dianhydride and p-phenylenediamine at a molar ratio of 1:1, and then add 60% of the total mass fraction of N,N-dimethylformamide. Stir the mixture at 25 °C for 40 minutes with the rotation speed controlled at 450 r / min. Slowly raise the temperature to 60 °C and react for 3 hours to carry out the amidation reaction. Add triethylamine with a molar amount of 40% of the pyromellitic dianhydride to neutralize the acid generated in the reaction. Subsequently, add 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester with a molar amount of 8% of the total molar amount of the raw materials, raise the temperature to 90 °C, and react for 4 hours at a stirring speed of 500 r / min to obtain a polyamic acid prepolymer solution. Then, add acetic anhydride with a molar amount twice that of the carboxyl groups in the polyamic acid prepolymer and pyridine with a molar amount of 0.5 times that of the acetic anhydride to the polyamic acid prepolymer solution, and react at 80 °C for 6 hours to obtain a modified polyimide solution. (2) Select alumina ceramic particles with a particle size of 80 nm, add them to deionized water according to the mass ratio of 1:15 with deionized water, and then add polyvinylpyrrolidone with a mass of 1% of the alumina ceramic particles. Stir at a stirring speed of 1000 r / min for 40 minutes, and then ultrasonically treat for 60 minutes at a power of 400 W to obtain an alumina ceramic suspension. Add hydroxymethylacrylamide to the alumina ceramic suspension, and the molar ratio of hydroxymethylacrylamide to the hydroxyl groups on the surface of the alumina ceramic is 2:1. Raise the temperature of the reaction system to 80 °C and react at a stirring speed of 500 r / min for 5 hours. Then, carry out vacuum filtration under a vacuum degree of -0.06 MPa, and subsequently wash with deionized water 3 - 5 times to remove impurities, and then dry at 60 °C for 8 hours to obtain modified alumina ceramic particles. (3) Add the modified alumina ceramic particles obtained in step (2) to the modified polyimide solution obtained in step (1) at a mass ratio of 11:1 of the modified polyimide solution to the modified alumina ceramic particles, and stir at a stirring speed of 800 r / min for 40 minutes to obtain a dispersion solution. Coat the dispersion solution on a stainless steel mold, and control the coating thickness at 0.5 mm. Subsequently, cure at 200 °C for 4 hours to obtain a packaging sheet.
[0019] Example 3 (1) Mix pyromellitic dianhydride and p-phenylenediamine in a molar ratio of 1:1, then add 60% of the total mass fraction of N,N-dimethylformamide, and mix and stir at 25 °C for 40 minutes with the rotation speed controlled at 450 r / min; slowly heat up to 60 °C and react for 3 hours to carry out an amidation reaction, and add 40% of triethylamine in terms of the molar amount of pyromellitic dianhydride to neutralize the acid generated by the reaction; then add 2-methyl-2-acryloyloxypropyl acrylate in an amount of 10% of the total molar amount of the raw materials, heat up to 90 °C, and react at a stirring speed of 500 r / min for 4 hours to obtain a polyamic acid prepolymer solution; then add acetic anhydride in an amount twice that of the carboxyl molar amount in the polyamic acid prepolymer and pyridine in an amount 0.5 times that of the molar amount of acetic anhydride to the polyamic acid prepolymer solution, and react at 80 °C for 6 hours to obtain a modified polyimide solution; (2) Select alumina ceramic particles with a particle size of 80 nm, add them to deionized water according to a mass ratio of 1:15 with deionized water, then add 1% of polyvinylpyrrolidone based on the mass of the alumina ceramic particles, stir at a stirring speed of 1000 r / min for 40 minutes, and then ultrasonically treat at a power of 400 W for 60 minutes to obtain an alumina ceramic suspension; add N-methylolacrylamide to the alumina ceramic suspension, and the molar ratio of N-methylolacrylamide to the surface hydroxyl groups of the alumina ceramic is 2.5:1, heat up the reaction system to 80 °C, react at a stirring speed of 500 r / min for 5 hours, then carry out vacuum filtration under a vacuum degree of -0.06 MPa, and then wash with deionized water 3 - 5 times to remove impurities, and then dry at 60 °C for 8 hours to obtain modified alumina ceramic particles; (3) Add the modified alumina ceramic particles obtained in step (2) to the modified polyimide solution obtained in step (1) according to a mass ratio of 13:1 of the modified polyimide solution to the modified alumina ceramic particles, stir at a stirring speed of 800 r / min for 40 minutes to obtain a dispersion solution; coat the dispersion solution on a stainless steel mold with the coating thickness controlled at 0.5 mm; then cure at 200 °C for 4 hours to obtain a packaging sheet.
[0020] Comparative Example 1: Do not add 2-methyl-2-acryloyloxypropyl acrylate, and the other steps are the same as those in Example 1.
[0021] Comparative Example 2: Do not add N-methylolacrylamide, and the other steps are the same as those in Example 1.
[0022] Comparative Example 3: Do not add modified alumina ceramic particles, and the other steps are the same as those in Example 1.
[0023] Performance Test Before the test, the encapsulated chip samples prepared in Examples 1-3 and Comparative Examples 1-3 were polished into wafers with a diameter of 25 mm using sandpaper with a particle size greater than 1000 mesh. The thermal conductivity of the samples was measured using a TPS 2200 thermal constants analyzer from HotDisk, Sweden. The tensile strength of the encapsulated chip samples prepared in Examples 1-3 and Comparative Examples 1-3 was measured at a speed of 50 mm / min with reference to the GB / T 13541-92 standard. The test results of the thermal conductivity and volume resistivity of the samples are shown in Table 1.
[0024] Table 1
[0025] As can be seen from Table 1, 2-methyl-2-acryloyloxypropyl 2,3-dihydroxypropyl acrylate was added to the dianhydride monomer and diamine monomer to prepare a modified polyimide; the ceramic was pretreated to obtain a ceramic suspension, and then hydroxymethylacrylamide was added. The hydroxymethyl in hydroxymethylacrylamide condensed with the hydroxyl groups on the ceramic surface to form a C-O-C bond, and at the same time, the amide group (-CONH2) was exposed on the surface to prepare a modified ceramic. The modified ceramic was added to the modified polyimide solution to prepare an encapsulated chip with high thermal conductivity, stable at a relatively high temperature, not prone to thermal deformation, and strong stability.
[0026] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present invention. Any reference signs in the claims should not be construed as limiting the claimed claim.
Claims
1. A high thermal conductivity PI / ceramic composite insulation encapsulation sheet, characterized in that, The high thermal conductivity PI / ceramic composite insulation encapsulation sheet is obtained by mixing a modified polyimide solution and modified ceramic particles in a mass ratio of 9-13:1 and then curing at high temperature; The modified polyimide solution is obtained by mixing a dianhydride monomer and a diamine monomer in a molar ratio of 1:1, and 5%-10% of the total molar amount of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, and then adding a catalyst for catalysis; The modified ceramic particles are obtained by adding hydroxymethylacrylamide to a ceramic suspension, mixing, filtering, washing, and drying; 2. The high thermal conductivity PI / ceramic composite insulation encapsulation sheet according to claim 1, wherein The catalyst includes acetic anhydride and pyridine; 3. The high thermal conductivity PI / ceramic composite insulation encapsulation sheet according to claim 1, wherein The ceramic particles include alumina ceramic particles, aluminum nitride ceramic particles, or silicon carbide ceramic particles; 4. A high thermal conductivity PI / ceramic composite insulation encapsulation sheet according to claim 1, characterized in that, The ceramic suspension is obtained by mixing ceramic particles and deionized water in a mass ratio of 1:10-15 and adding 1%-3% of the dispersant based on the mass of the ceramic particles; 5. The high thermal conductivity PI / ceramic composite insulation encapsulation sheet according to claim 4, characterized in that, The dispersant is sodium polyacrylate, sodium hexametaphosphate, or polyvinylpyrrolidone; 6. A preparation method of a high thermal conductivity PI / ceramic composite insulation encapsulation sheet, characterized in that, It includes the following preparation steps: (1) Mix the dianhydride monomer and the diamine monomer in a molar ratio of 1:1, then add 60%-70% of the organic solvent based on the total mass fraction, mix and stir at 20°C - 30°C for 30 - 60 minutes, and control the rotation speed at 300 - 500 r / min; slowly raise the temperature to 50 - 60°C, react for 2 - 3 hours to carry out an amidation reaction, and add 30%-50% of the acid-binding agent based on the molar amount of the dianhydride monomer to neutralize the acid generated by the reaction; then add 5%-10% of the total molar amount of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, raise the temperature to 80 - 90°C, stir and react for 3 - 4 hours to obtain a polyamic acid prepolymer solution; then add a catalyst to the polyamic acid prepolymer solution and react at 80 - 100°C for 4 - 6 hours to obtain a modified polyimide solution; (2) Select ceramic particles with a particle size of 50 - 100nm, add them to deionized water according to the mass ratio of 1:10 - 15 to the deionized water, then add 1%-3% of the dispersant based on the mass of the ceramic particles, stir at a stirring speed of 800 - 1000 r / min for 20 - 40 minutes, and then ultrasonically treat at a power of 300 - 400W for 40 - 60 minutes to obtain a ceramic suspension; add hydroxymethylacrylamide to the ceramic suspension, and the molar ratio of hydroxymethylacrylamide to the hydroxyl groups on the ceramic surface is 1 - 2.5:1, raise the temperature of the reaction system to 70 - 80°C, react at a stirring speed of 500 - 600 r / min for 4 - 5 hours, and then filter, wash, and dry to obtain modified ceramic particles; (3) Add the modified ceramic particles obtained in step (2) to the modified polyimide solution obtained in step (1) according to the mass ratio of the modified polyimide solution to the modified ceramic particles of 9 - 13:1, and stir at a stirring speed of 600 - 800 r / min for 20 - 40 minutes to obtain a dispersion solution; Coat the dispersion solution on a stainless steel mold, and control the coating thickness at 0.2 - 0.5mm; Then cure at high temperature to obtain an encapsulation sheet.
7. The preparation method of a highly thermally conductive PI / ceramic composite insulating encapsulation sheet according to claim 6, wherein, In the step (1), a catalyst is added to the polyamic acid prepolymer solution, and the reaction is carried out at 80-100 °C for 4-6 hours to obtain a modified polyimide, including: adding acetic anhydride in an amount of 1.5-2 times the molar amount of carboxyl groups in the polyamic acid prepolymer and pyridine in an amount of 0.5-1 times the molar amount of acetic anhydride as a catalyst to the polyamic acid prepolymer solution, and carrying out the reaction at 80-100 °C for 4-6 hours to obtain a modified polyimide.
8. The preparation method of a highly thermally conductive PI / ceramic composite insulation encapsulation sheet according to claim 6, characterized in that, In the step (1), the preferred value of 2-methyl-2-acryloyloxypropyl dihydrogen phosphate in the total molar amount is 8%.
9. The preparation method of a high thermal conductivity PI / ceramic composite insulation encapsulation sheet according to claim 6, characterized in that, In the step (2), the molar ratio of hydroxymethylacrylamide to the hydroxyl groups on the ceramic surface is preferably 2:
1.
10. The preparation method of a highly thermally conductive PI / ceramic composite insulation encapsulation sheet according to claim 6, characterized in that, In the step (3), the mass ratio of the modified polyimide solution to the modified ceramic is preferably 11:1.
Citation Information
Cited By
Preparation method of insulating high-temperature-resistant polyimide-ceramic composite material
CN121249150A
Preparation method of insulating high-temperature-resistant polyimide-ceramic composite material
CN121249150B